The beautiful : illustrations for fashion and style - Krull, Anneke (Berlin : Gestalten, 2010)
Illustration is one of today's fastest-growing creative disciplines, and its versatility has made it a key element in fashion, lifestyle, editorial design and advertising. 'The Beautiful' presents the work of the most promising illustrators in the areas of fashion, lifestyle, editorial design and commercial illustration.
boek